Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(4x^4-16-4x^2-16x\)
\(=4x^2\left(x^2-1\right)-16\left(1+x\right)\)
\(=4x^2\left(x+1\right)\left(x-1\right)-16\left(x+1\right)\)
\(=\left(x+1\right)\left[4x^2\left(x-1\right)-16\right]\)
\(=\left(x+1\right)4\left[x^2\left(x-1\right)-4\right]\)
Nguyễn Văn Tuấn AnhNs r, không biết thì not làm
\(4x^4-16-4x^2-16x\)
\(=4x^2\left(x^2-1\right)-16\left(x+1\right)\)
\(=4x^2\left(x-1\right)\left(x+1\right)-16\left(x+1\right)\)
\(=\left(x+1\right)\left[4x^2\left(x-1\right)-16\right]\)
\(=4\left(x+1\right)\left[x^2\left(x-1\right)-4\right]\)
\(=4\left(x+1\right)\left[x^3-x^2-4\right]\)
\(=4\left(x+1\right)\left[x^3+x^2+2x-2x^2-2x-4\right]\)
\(=4\left(x+1\right)\left[x\left(x^2+x+2\right)-2\left(x^2+x+2\right)\right]\)
\(=4\left(x+1\right)\left(x-2\right)\left(x^2+x+2\right)\)
\(x^4-4x^3+8x^2-16x+16 \)
\(=x^3\left(x-2\right)-2x^2\left(x-2\right)+4x\left(x-2\right)-8\left(x-2\right)\)
\(=\left(x-2\right)\left(x^3-2x^2+4x-8\right)\)
\(=\left(x-2\right)\left[x^2\left(x-2\right)+4\left(x-2\right)\right]\)
\(=\left(x-2\right)^2\left(x^2+4\right)\)
\(x^3-2x^2+x-xy^2\)
\(=x\left(x^2-2x+1-y^2\right)\)
\(=x\left[\left(x-1\right)^2-y^2\right]\)
\(=x\left(x-1-y\right)\left(x-1+y\right)\)
a,x4-4x3+8x2-16x+16
=x4-4x3+4x2+4x2-16x+16
=x2.(x-2)2+4.(x-2)2
=(x-2)2(x2+4)
`a. =4(x^2+4x+3)=4(x^2+3x+x+3)=4(x+3)(x+1)`
`b. =x^2+8x-7x-56=x(x+8)-7(x+8)=(x+8)(x-7)`
`c. =x^2-9x+8x-72=x(x-9)+8(x-9)=(x-9)(x+8)`
`d. =(x-y)^2-9=(x-y-3)(x-y+3)`
x^4 - 4x^3 - 8x^2 - 16x + 16
= x^4-8x^2+16-4x^3-16x
= ( x^2+4)^2 - 4x(x^2+4 )
= ( x^2 + 4 )(x^2 + 4 - 4x)
= (x^2 + 4 )( x - 2 )^2
-4x2 + 16x + 9
= -4x2 - 2x + 18x + 9
= -2x(2x + 1) + 9(2x + 1)
= (9 - 2x)(2x + 1)